Across-country genetic evaluation of dairy cattle in Sub-Saharan Africa - CGIAR Research Program on Livestock (2020)
End of research phase (discovery/proof of concept) of a genomic tool and methodological approach that will increase the accuracies of genetic predictions, thus increasing rates of genetic gain and benefits to smallholder farmers.